Urban strategic foresight in European territories – Lessons from Geneva and Luxembourg - Panos Mantziaras (Agathón)
The contribution offers an overview of the international consultations held over the past decade in Geneva and Luxembourg as part of the ecological transition process initiated in their territories. The first part frames the context within which the consultations occurred, reporting on the evolution of regional environmental conditions. The second part briefly describes the ‘strategic foresight’ method in both consultations. The third part reports on the outcomes of the consultations and proposals to national and local governments and their transboundary counterparts for methods, tools and devices to tackle the current environmental crisis and develop coordinated projects at all scales. The overall objective was to steer local communities towards zero-carbon development paths and climate change adaptation. The text concludes with some reflections on the timeliness of strategic foresight as a valuable tool for building a renewed critical role of the architectural discipline in a context of social and environmental uncertainty. It argues that design approaches, methodologies and tools can no longer be based on the ideology of anthropocentric dominance over the biosphere: instead, architecture must sustain a primary role in becoming a spokesperson for the crucial challenges of our time.